2022
DOI: 10.1038/s41598-022-16063-z
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating changes in growth and pigmentation of Cladosporium cladosporioides and Paecilomyces variotii in response to gamma and ultraviolet irradiation

Abstract: Melanin-containing fungi (black molds) have the capacity to thrive under extreme environmental conditions such as the elevated radiation levels inside the former Chernobyl reactors. These fungi have been hypothesized to grow toward and use gamma radiation as an energy source, but the literature does not clearly address which energies of the electromagnetic spectrum, if any, positively affect fungal growth. The goal of this work was to characterize the response of non-melanized and melanized fungi to two distin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
2
1
Order By: Relevance
“…For example, we found a reduction in the abundance of the fungus Cladosporium in response to solar radiation. While Cladosporium species are melanized filamentous fungi, and melanin can typically protect them from UV radiation, our results contradicted this expectation [43]. Interestingly, we observed an increase in endophytic Pseudomonas species favored by solar radiation, possibly due to their pigment-producing abilities.…”
Section: Discussioncontrasting
confidence: 84%
“…For example, we found a reduction in the abundance of the fungus Cladosporium in response to solar radiation. While Cladosporium species are melanized filamentous fungi, and melanin can typically protect them from UV radiation, our results contradicted this expectation [43]. Interestingly, we observed an increase in endophytic Pseudomonas species favored by solar radiation, possibly due to their pigment-producing abilities.…”
Section: Discussioncontrasting
confidence: 84%
“…In fact, the poorly documented reports on the production of citreoviridin A, viriditoxin, cytochalasin D and citrinin H1 mycotoxins by this genus may be attributed to misidentification or contaminations by mycotoxin- producing species. Cladosporium harbors species that can grow at oligotrophic conditions and at fluctuating temperatures(48), which together with their resistant to irradiation(49), supports their robustness in bioremediation applications.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that an increase in the dose of gamma rays led to a consistent increase in the production of PKS-based pigment melanin in Cryomyces antarcticus [ 311 ]. Exposure to ultraviolet irradiation led to an increase in pigmentation in both the melanin-containing Cladosporium cladosporioides and the non-melanized fungus Paecilomyces variotii [ 312 ]. However, in these cases, it is important to correlate how strongly the changes in Y SM occurred in response to different doses of SP.…”
Section: Regulation Of Sm Production In Fungi According To the Piano ...mentioning
confidence: 99%